Characterization of actinide targets for fission cross section measurements - Diakaki, M.; Vlastou, R.; Kokkoris, M.; Karadimos, D.; Lagoyannis, A.; Axiotis, M.; Ioannides, K.; Stamoulis, K. (HNPS Advances in Nuclear Physics, 2012)
In this work the characterization of thin actinide targets ( 237Np, 238U, 235U), man- ufactured for measurements of fission cross section, will be presented. The determi- nation of the mass of the actinide content of each target has been performed via alpha spectrometry, utilizing two SSB detectors, with 50mm2 and 3000mm2 active surface, in order to combine good resolution and good statistics respectively and obtain a smaller error in the final mass result. The impurities of the targets were quantitatively estimated with the same technique. The homogeneity of the samples was examined with two independent methods. Firstly, RBS measurements were per- formed using a proton beam of 2 MeV, provided by the 5.5 MV Tandem Van de Graaff accelerator of the N.C.S.R. ”Demokritos”. The thickness of each target was quantitatively estimated at various points. Secondly, CR-39 plastic track detectors were used to measure the alpha tracks from the surface of the targets and provide an image of the activity of the surface.